On the interactions among environmental degradation, energy consumption and economic growth: a time-frequency analysis using wavelets - Abdi Ali, Dahir; Mohamed Dahir, Ahmed; Midi, Habshah (Taylor and Francis Group, 2022)
This paper aims to investigate the interactions between CO2 emissions, economic growth and energy consumption in India for 1970–2017 within the time–frequency domain using wavelet techniques. The results show that the interaction between energy consumption and CO2 emissions is strong and varies significantly across time–frequency bands, indicating that the energy consumption leads to environmental degradation. The negative effect of economic growth on CO2 emissions is only statistically significant in the short run. In addition, the findings reveal a positive association between economic growth and energy consumption across time–frequency bands, demonstrating energy consumption increases economic growth, which in turn heightens the CO2 emissions. There should be improved energy use and reduced CO2 emissions.